TRANSFORMING GROWTH FACTOR-BETA-1 BY DIFFERENT CLINICAL COURSE OF ISCHEMIC HEART DISEASE AFTER CORONARY ARTERY BYPASS GRAFTING SURGERY - K. V. Korzhenevskaya; N. A. Gavrischeva; A. V. Panov; T. P. Ses’; M. Z. Alugishvili; V. V. Kozlov (Медицинская иммунология)
The article presents data on the levels of transforming growth factor-beta-1 (TGF-β1) in blood serum and their correlation with clinical features of coronary artery disease in 130 patients with non-ST elevation acute coronary syndrome (non-ST ACS), who underwent coronary artery bypass grafting surgery (CABG), at different terms (6, 12, 24, 48 mo) following surgical intervention. It was revealed that a recurrent myocardial ischemia is associated with increased levels of TGF-β1. Following CABG, the TGF-β1 levels are significantly increasing, and reach their preoperative values by the end of observation period.